ChemInform Abstract: Electrophilic Amination of Fluoroalkyl Groups on Azodicarboxylate Derivatives. Issue 26 (June 2015) - Mamone, Marius; Morvan, Estelle; Milcent, Thierry; Ongeri, Sandrine; Crousse, Benoit
Abstract The obtained fluoroalkylhydrazines can be further deprotected or N‐alkylated.